Training and development as a driver of knowledge management in Palestinian higher education institutions - Sadeq, Abdallah I A; Juhdi, Nurita; Abdul Hamid, Zabeda (Human Resource Management Academic Research Society (HRMARS), 2026)
This study investigates the effect of training and development on knowledge management within higher education institutions, focusing on Palestinian universities as a knowledge intensive and resource-constrained context. While prior research has acknowledged the role of human resource management in enhancing organizational outcomes, limited empirical evidence exists on how specific HRM practices, particularly training and development, influence knowledge management in higher education settings. A quantitative research design was adopted using a cross-sectional survey of 310 full-time academic staff. The data were analysed using partial least squares structural equation modelling (PLS-SEM). The results indicate that training and development has a positive effect on knowledge management, with the model explaining a substantial proportion of variance (R² = 0.463). The effect size (f² = 0.070) suggests that training and development contributes meaningfully to improving knowledge-related processes within universities. The findings highlight the importance of structured training programs in enhancing employees’ competencies, promoting knowledge sharing, and strengthening organizational learning. This study contributes to the literature by providing empirical evidence from an underexplored context and by focusing on a single HRM dimension to better understand its impact on knowledge management. Practically, the study offers valuable insights for university leaders and policymakers, emphasizing the need to invest in continuous training initiatives to support knowledge management and improve institutional performance